EXTENT OF UTILIZATION OF e-LEARNING TOOLS AS TEACHING S T R AT E G I E S B Y B U S I N E S S E D U C AT O R S I N T E RT I A RY INSTITUTIONS IN SOUTH-EASTNIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The study investigated the utilization of e-learning tools as teaching strategies by businesseducators in tertiary institutions in south east Nigeria. Two research questions were posedand answered while two null hypotheses were formulated and tested at 0.05 level ofsignificance. A descriptive survey design was adopted. A total of 200 business educators in14 tertiary institutionsin South East, Nigeria made up the population of the study. No samplewas taken, as the number was sizeable for the researchers to handle. A structured 25-itemvalidated questionnaire was used for data collection. The reliability of the instrument wasensured using pilot test technique, which was analyzed using Cronbach alpha method andyielded reliability co-efficient of 0.76. Data related to the research questions were analyzedusing mean and standard deviation while z-test statistic was used to test the null hypotheses.The findings from the study revealed that multi-media and internet tools were used asteaching strategies but to a moderate extent. The study also revealed that type of institutionsdo not significantly affect the utilization of e-learning tools (multimedia and internet) asteaching strategies in tertiary institutions in south east, Nigeria. It was concluded thatbusiness educators utilized multimedia and internet tools as teaching strategies to amoderate extents as a result of insufficient training and retraining given to them. Toencourage the use of e-Learning tools as teaching strategies by business educators, it wasrecommended, among others, that business educators should develop themselves by inservice training. They should also constantly use e-Learning tools provided by thegovernment and administrators of institutionsin teaching tasks.
Keywords: e-Learning tools, teaching strategy, utilization, multimedia, internet, business educators